Exploring bioactive phytochemicals as ULK1 activators for enhancing cytoprotective autophagy in amyotrophic lateral sclerosis - Anjum, Farah; Hawsawi, Nahed; Almalki, Abdulraheem Ali; Shamsi, Anas; Hulbah, Maram Jameel; Bakhuraysah, Maha; Alsharif, Abdulaziz; Mohammad, Taj (Frontiers in Pharmacology, 2025)
BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder that results in the degeneration of motor neurons and is typically linked to toxic aggregates of mutant superoxide dismutase 1 (SOD1) protein. As autophagy is critical for the removal of these toxic protein aggregates, stimulating autophagy has emerged as a promising therapeutic approach for ALS. Unc-51-like kinase 1 (ULK1) is a key regulator of autophagy and has been shown to have the potential to prevent ALS pathology when activated. However, synthetic ULK1 activators are frequently limited by toxicity and suboptimal pharmacokinetic profiles. This study aimed to identify natural ULK1 activators using a systematic virtual screening approach for potential ALS therapy.Materials and MethodsThis study employed a comprehensive virtual screening approach to identify phytochemicals capable of activating ULK1. Natural compounds from the IMPPAT database were screened using molecular docking, followed by pan-assay interference compounds (PAINS) filtering, pharmacokinetic profiling, and density functional theory (DFT) analysis. Further, biological activity was predicted using the PASS tool, and candidate molecules were subjected to molecular dynamics (MD) simulations, essential dynamics, and binding free energy calculations via MM-PBSA.ResultsThe systematic screening in this study identified Candidine and Delavinone as high-affinity binders with reference to BL-918, proposing them as potential activators of ULK1. Both compounds demonstrated favorable drug-likeness, stable interactions with ULK1 in MD simulations, and promising ALS-relevant activity profiles. Essential dynamics and MM-PBSA further supported the binding stability and energetic favorability of these interactions.ConclusionCandidine and Delavinone emerge as promising phytochemical activators of ULK1 with potential therapeutic relevance for ALS. These findings warrant further experimental validation and preclinical studies to explore their efficacy in autophagy modulation and neuroprotection.